Legal Analysis of the Position of Exoneration Clause in the Contract Legal System in Indonesia - Danial Syah (Faculty of Law, Universitas Pekalongan, 2021)
The development of social life and human interaction methods results in changes in the nature of laws. The forms of agreements or contracts in the early stages of human life were characterized by strong emotional ties. Written contracts were merely created as a reminder of their previous contractual relationships, not necessarily to bind parties to an agreement. However, as society's interactions expanded to reach the external world beyond their domicile, humans began to consider how to engage in contracts without being disadvantaged, especially by parties providing facilities, such as financing or other services, who held greater bargaining power than others. This led to the creation of pre-prepared contract documents without the consent of the other party, which is known as the